Model based approach for planning dynamic integration of renewable energy in a transitioning electricity system. (February 2019) - Sharma, Tarun; Balachandra, P.
Highlights: Approach for dynamic integration of renewable energy in electricity system. Generation expansion and scheduling model with explicit capacity utilization. Renewable energy penetration scenarios for Indian electricity system. Quantification of rate at which renewable capacity substitutes conventional capacity. Abstract: Reality of climate change threats have spurred mitigation interventions across the world. For electricity sector, the interventions are predominantly in terms of mainstreaming renewable energy sources. Consequently, there is a consistent increase in the share of renewable energy-based electricity systems which has caused emergence of several new challenges. The challenges have emerged both with respect to planning and management of the transitioning electricity systems. These new challenges are because of shift away from supply-chain influenced conventional energy resource supply to nature influenced dynamic renewable energy resource supply; shift from conventional firm power to renewable intermittent power; operational complexities due to frequent and steeper ramps; and need for matching dynamic demand for power. We propose, develop and validate a novel approach for better representation of these resource-supply-demand dynamics in evolving suite of generation expansion models with operational details. First, we discuss development of an electricity generation expansion planning model with operational details. Second, to model the dynamic nature of renewable energy resources and demand for power, we develop an approach for generating annual wind and solar resource profiles, and representative load curves respectively, and harmonizing them before they are fed into the generation expansion model. We validate this approach using India's electricity system data and use the model to evaluate implications of varying levels of renewable energy integration. We find that this increased penetration of renewable energy while bringing significant climate change benefits creates substantial capacity redundancy leading to lower capacity utilization of the overall system.